Ambiguitas Hukum Kepailitan terhadap Perseroan Perorangan: Urgensi Pengaturan Khusus dalam Undang-Undang Kepailitan - Parapat, Henry Anderson; Djun’astuti, Erni (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
The Sole Proprietorship Company (Perseroan Perorangan), introduced by the Job Creation Law, created a single-owner legal entity with limited liability. This novel structure, however, generates significant legal ambiguities within national bankruptcy law, particularly regarding the separation of corporate and personal assets. This study employs a normative juridical method to analyze these ambiguities and proposes a necessary regulatory reconstruction to ensure legal certainty. Findings reveal that the absence of specific bankruptcy norms for Sole Proprietorship Companies directly facilitates the harmful practice of serial bankruptcy. This maneuver involves repeated corporate liquidation by the sole owner to evade financial obligations, thus undermining the principle of good faith and eroding creditor trust. To address this, the research recommends a legal reconstruction built on three critical pillars: rigorous testing of the owner's good faith, mandatory strengthening of asset separation, and the strict application of the Piercing the Corporate Veil (PCV) doctrine. This reconstruction is vital to ensure the Sole Proprietorship Company genuinely serves to empower Micro and Small Enterprises (MSEs), rather than functioning as a loophole for corporate abuse.